Advancement in lipid-based nanocomposites for theranostic applications in lung carcinoma treatment - Viola Colaco; Amrita Arup Roy; Gaurisha Alias Resha Ramnath Naik; Arijit Mondal; Srinivas Mutalik; Namdev Dhas (Elsevier, 2024)
On a global scale, lung cancer remains a common malignancy and is largest cause of many deaths related to cancer. Despite the significant advancements in lung cancer diagnostic and therapeutic approaches, many individuals exhibit resistant responses to proven therapies. This focuses on the critical need for novel therapeutic methods to be developed and innovated. Recently, nanotechnology has gained a lot of importance for treating malignancy as it helps improve drug delivery, specificity, reduced dose, and efficient elimination. Lipid nanoparticles (LNPs) are nanocarriers with low particle size, which can be modified for specific delivery. The current review focuses on the significance and application of lipid-based theranostic nanoparticles for cancer therapy, components, method of preparation and factors affecting lipid nanoparticle preparation, along with the clinical trials and patents of LNPs. Therapeutic applications in lung cancer therapy include Chemotherapy, photodynamic therapy, immunotherapy, gene therapy, photothermal therapy, and sonodynamic therapy. Diagnostic applications like SPECT, CT, MRI, PET, Optical fluorescence imaging and NIR. As LNPs are being used more frequently in lung cancer therapy, the ongoing research helps in offering solutions to overcome the issues by conventional treatments. Due to their adaptability to customized medical procedures and the use of numerous components, they hold the potential for treating lung cancer. In conclusion, LNPs offer a viable strategy for treating lung cancer by boosting bioavailability, promoting medication delivery, and removing obstacles. For individualised medicine, they can encapsulate a range of therapeutic, such as immunomodulatory medicines, siRNA, and chemotherapeutic medications. Additional study and clinical validation are required to address scalability, long-term safety, and optimised manufacturing techniques for effective application in lung cancer therapy.